Evaluation of Silybin Nanoparticles against Liver Damage in Murine Schistosomiasis mansoni Infection - Daniel Figueiredo Vanzan; Ester Puna Goma; Fernanda Resende Locatelli; Thiago da Silva Honorio; Priscila de Souza Furtado; Carlos Rangel Rodrigues; Valeria Pereira de Sousa; Hilton Antônio Mata dos Santos; Flávia Almada do Carmo; Alice Simon; Alexandre dos Santos Pyrrho; António José Ribeiro; et al. (MDPI AG, 2024)
Silybin (SIB) is a hepatoprotective drug known for its poor oral bioavailability, attributed to its classification as a class IV drug with significant metabolism during the first-pass effect. This study explored the potential of solid lipid nanoparticles with (SLN-SIB-U) or without (SLN-SIB) ursodeoxycholic acid and polymeric nanoparticles (PN-SIB) as delivery systems for SIB. The efficacy of these nanosystems was assessed through in vitro studies using the GRX and Caco-2 cell lines for permeability and proliferation assays, respectively, as well as in vivo experiments employing a murine model of Schistosomiasis mansoni infection in BALB/c mice. The mean diameter and encapsulation efficiency of the nanosystems were as follows: SLN-SIB (252.8 ± 4.4 nm, 90.28 ± 2.2%), SLN-SIB-U (252.9 ± 14.4 nm, 77.05 ± 2.8%), and PN-SIB (241.8 ± 4.1 nm, 98.0 ± 0.2%). In the proliferation assay with the GRX cell line, SLN-SIB and SLN-SIB-U exhibited inhibitory effects of 43.09 ± 5.74% and 38.78 ± 3.78%, respectively, compared to PN-SIB, which showed no inhibitory effect. Moreover, SLN-SIB-U demonstrated a greater apparent permeability coefficient (25.82 ± 2.2) than PN-SIB (20.76 ± 0.1), which was twice as high as that of SLN-SIB (11.32 ± 4.6) and pure SIB (11.28 ± 0.2). These findings suggest that solid lipid nanosystems hold promise for further in vivo investigations. In the murine model of acute-phase Schistosomiasis mansoni infection, both SLN-SIB and SLN-SIB-U displayed hepatoprotective effects, as evidenced by lower alanine amino transferase values (22.89 ± 1.6 and 23.93 ± 2.4 U/L, respectively) than those in control groups I (29.55 ± 0.7 U/L) and I+SIB (34.29 ± 0.3 U/L). Among the prepared nanosystems, SLN-SIB-U emerges as a promising candidate for enhancing the pharmacokinetic properties of SIB.